2023
DOI: 10.1007/s00467-023-05913-1
|View full text |Cite|
|
Sign up to set email alerts
|

Rituximab-associated hypogammaglobulinemia in children with idiopathic nephrotic syndrome: results of an ESPN survey

Abstract: Background There is paucity of information on rituximab-associated hypogammaglobulinemia (HGG) and its potential infectious consequences in children treated for idiopathic nephrotic syndrome (INS). Methods A survey was distributed by the European Society Pediatric Nephrology to its members. It addressed the screening and management practices of pediatric nephrology units for recognizing and treating RTX-associated HGG and its morbidity and mortality. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Furthermore, there were no cases of RTX discontinuation due to these adverse events. While hypogammaglobulinemia events were less frequent in our study, previous studies have shown that hypogammaglobulinemia is a common complication of RTX treatment in children with SDNS [10,14,33]. This event might have been underestimated in our study because we did not routinely check immunoglobulin levels.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Furthermore, there were no cases of RTX discontinuation due to these adverse events. While hypogammaglobulinemia events were less frequent in our study, previous studies have shown that hypogammaglobulinemia is a common complication of RTX treatment in children with SDNS [10,14,33]. This event might have been underestimated in our study because we did not routinely check immunoglobulin levels.…”
Section: Discussioncontrasting
confidence: 60%
“…In a European survey, 65% and 59% of centers reported regularly monitoring immunoglobulin G levels before and after RTX administration [33]. While a retrospective study showed no signi cant association between hypogammaglobulinemia severity and infection [15], another study reported that 80% of patients with severe infections had hypogammaglobulinemia [33]. Clinicians need to monitor impaired immune function following RTX treatment, particularly in younger patients at higher risk for hypogammaglobulinemia, as reported in previous studies [10,34].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Authors reported that hypogammaglobulinemia was observed in around 35% of treated subjects. However that hypogammaglobulinemia may persist several months after the last rituximab infusion is commonly reported, but if the hypogammaglobulinemia would be related to a major risk of severe infections is still to be completely defined ( 58 ).…”
Section: Monoclonal Anti-cd20 Antibodiesmentioning
confidence: 99%
“…However, unlike other immunosuppressive therapies, there is a lack of long-term follow-up data on RTX use in INS. To address this gap, the European Society of Pediatric Nephrology (ESPN) conducted a survey in 84 centers, involving 1328 children, to gather information on RTX-associated hypogammaglobulinemia and its potential consequences in INS 9 . This survey provides valuable insights as it reflects the common practice of pediatric nephrologists outside of research protocols and includes a robust number of patients.…”
mentioning
confidence: 99%